2000
DOI: 10.1074/jbc.m005369200
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of a Glycoprotein 120 V3 Loop Peptide to HIV-1 Neutralizing Antibodies

Abstract: The structural and antigenic properties of a peptide ("CRK") derived from the V3 loop of HIV-1 gp120 protein were studied using NMR and SPR techniques. The sequence of CRK corresponds to the central portion of the V3 loop containing the highly conserved "GPGR" residue sequence. Although the biological significance of this conserved sequence is unknown, the adoption of conserved secondary structure (type II ␤-turn) in this region has been proposed. The tendency of CRK (while free or conjugated to protein), to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…A strong correlation between the structure stability and the a¤nity between protein subdomains has been found from SPR data [2] and a combined use of SPR and NMR measurements has been proposed for investigating peptide^antibody [3,4] and virus^receptor interactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…A strong correlation between the structure stability and the a¤nity between protein subdomains has been found from SPR data [2] and a combined use of SPR and NMR measurements has been proposed for investigating peptide^antibody [3,4] and virus^receptor interactions [5].…”
Section: Introductionmentioning
confidence: 99%
“…This paper describes experiments addressing the question: can antibodies elicited against REPs bind hIgs in vitro ? The rationale for asking this question was that previously, structural similarities between REPs and hIgs were discovered [10–12]. Amino acid sequence homologies were found between some portions of HIV‐1, HIV‐2 and SIV envelope proteins and hIg V H regions [13].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of gp120 and, possibly, other retroviral envelope proteins (REPs) to bind certain antigenic epitopes, including idiotopes, may be related to the fact that REPs have a number of antibody‐like structural properties. REPs are folded into loops that resemble Ig domains, containing three constant (C1–C3) and three variable (V1–V3) domains [10–12]. By computer‐assisted amino acid homology search, we have previously shown that certain oligopeptides are shared between the V3 loop of some HIV‐2 and SIV isolates, and the tetrapeptide sequences between positions 56 and 59 on the V region of human Igs (hIgs) heavy‐chain V regions (V H ) coded by a small group of related Ig V region genes (V H 3–30, V H 3–30.3 and V H 3–33 [13]).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have followed the second approach to generate a V3 loop derivative. NMR studies on free V3 loop peptides report the presence of a relatively unstructured ensemble of V3 molecules in solution [17,[23][24][25][26]. NMR and crystal structures have been solved for V3 peptides in complex with a number of neutralizing antibodies [27][28][29][30], including mAb 447-52D [31].…”
Section: Introductionmentioning
confidence: 99%